Priority modern scientific trends and approaches in physical education research: bibliometric analysis of scientometric databases - Nataliia Saltan; Oleh Olkhovyi; Ihor Fishchuk; Oleksandr Saltan; Yulia Semenova; Olena Orlenko (Слобожанський науково-спортивний вісник)
Background and Study Aim. With the advent of software tools for the automatic selection and analysis of large amounts of information, researchers have been able to significantly speed up the search for relevant literature. Scientific and bibliographic databases and tools for their visualisation allow to optimise the data search process and simplify the analysis of the information obtained. The purpose of this study was to identify and analyse popular modern areas of research in the field of physical education and sports through a multilayer bibliometric analysis of scientific publications from the Scopus scientometric database.